2020
DOI: 10.1186/s41239-020-00224-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of students evaluation of teaching: a text analysis of the teachers qualities by gender

Abstract: Today, modern educational models are concerned with the development of the teacher-student experience and the potential opportunities it presents. User-centric analyses are useful both in terms of the socio-technical perspective on data usage within the educational domain and the positive impact that data-driven methods have. Moreover, the use of information and communication technologies (ICT) in education and process innovation has emerged due to the strategic perspectives and the process monitoring that hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 58 publications
0
42
0
Order By: Relevance
“…The definition of emotional valence and its implication in respect to the different studied phenomenon or areas of its application, particularly within the educational domain, has been illustrated in the literature (Kort et al, 2001;Litman & Forbes-Riley, 2004;Okoye et al, 2020;Shen et al, 2009;Tian et al, 2010Tian et al, , 2018. As demonsttarted in this study, such type of analysis (allied to the text mining) is achieved by leveraging the underlying information (textual data) that are contained in the readily available datasets to draw useful insights or patterns about the population.…”
Section: Experiences and Emotional Well-being Of Teachers And Studentsmentioning
confidence: 97%
See 2 more Smart Citations
“…The definition of emotional valence and its implication in respect to the different studied phenomenon or areas of its application, particularly within the educational domain, has been illustrated in the literature (Kort et al, 2001;Litman & Forbes-Riley, 2004;Okoye et al, 2020;Shen et al, 2009;Tian et al, 2010Tian et al, , 2018. As demonsttarted in this study, such type of analysis (allied to the text mining) is achieved by leveraging the underlying information (textual data) that are contained in the readily available datasets to draw useful insights or patterns about the population.…”
Section: Experiences and Emotional Well-being Of Teachers And Studentsmentioning
confidence: 97%
“…Technically, we used the get_nrc_sentiment function in R to extract the different (emotional valence) scores considering the responses by the students and their teachers. Typically, the get_nrc_sentiment functions by obtaining and quantifying (polarization) the intensities of the different terms (emotions) using the positive ( +), neutral (0) and negative (-) values (Litman & Forbes-Riley, 2004;Okoye et al, 2020) to represent each relevant term it finds in each case. In Fig.…”
Section: Experiences and Emotional Well-being Of Teachers And Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome of the exploratory study comprised of a survival model (Wen et al, 2014 ) that was built as a predictive/monitoring tool for determining the efficacy of certain human-expressions or language-behaviours (e.g., the impact of students' opinions in the MOOCs environment) based on the probability of certain events happening. Also, taking into account the connectedness between the text mining technique (e.g., sentiment analysis) and machine learning or classification models (Ofli et al, 2016 ), the study of Dey et al ( 2016 ) notes that the sentiments which are often found in the comments or feedbacks (e.g., SET) can be categorized by polarity (i.e., positive, neutral, or negative Kalaivani, 2013 ; Litman & Forbes-Riley, 2004 ; Okoye et al, 2020 ), and then utilized to provide valuable pointers or indicators in connection to the various reasons or purposes for which the datasets are analyzed (e.g., the advances in teaching analytical methods and/or students’ evaluation of teaching described in this study). Besides, the authors (Dey et al, 2016 ) also used a statistical method that supports the K-nearest neighbour (KNN) (Abu Alfeilat et al, 2019 ; Ghosh et al, 2020 ; Viji et al, 2020 ) and Naïve Bayes’(Zhou et al, 2020 ) supervised machine learning algorithms to capture the different words/sentence polarities and elements of the subjective styles or patterns.…”
Section: Background Informationmentioning
confidence: 99%
“…Along these lines, this study shows that there is a need for innovative methods or approaches, such as the EPDM + ML model proposed in this paper, for extraction of educational-based information from the unprecedented datasets recorded and stored about the students' evaluation/recommendation of the teaching–learning performances, to help transliterate them into actionable plans for education in general. In our analysis, we extended the educational process and data mining (EPDM) model proposed in Okoye et al, ( 2020 ) to show how the amalgamation of the Text mining and Machine learning techniques which we grounded on the descriptive decision theory (Baucells & Katsikopoulos, 2011 ; Chandler, 2017 ), can be used to analyze the (educational) data (SET) towards improvement of the end-to-end teachers-students learning process and interactions within the higher educational setting. To this end, we proposed an educational process and data mining + machine learning (EPDM + ML) model for fostering the teaching analytics and performance evaluation.…”
Section: Introductionmentioning
confidence: 99%